A Brief Task to Assess Individual Differences in Fat Discrimination. Issue 4 (21st May 2016) - Donovan, Joseph D.; Keller, Kathleen L.; Tepper, Beverly J.
Abstract: Fat discrimination ability varies across individuals and may be related to individual differences in fat preference and dietary behavior. The objective of this study was to develop a brief fat discrimination task using salad dressings varying in canola oil content, in a difference from control format. First, 74 subjects were identified as fat discriminators or fat non‐discriminators based on a screening task. Subjects were also classified as non‐, medium‐ or super‐tasters of the bitter compound, 6‐n‐propylthiouracil (PROP) that has previously been linked to differences in fat perception. Then, all subjects participated in a four‐sample difference from control task where they assessed the degree of difference between the test samples and a blind control. Results showed that the more sensitive groups (PROP super‐tasters and fat discriminators) were able to discern both 30 and 40% fat samples from the 55% fat blind control, but the less sensitive groups (PROP non‐ and medium tasters, and fat non‐discriminators) could only discern the 30% fat sample from the 55% fat blind control. These data suggest that the four‐sample difference‐from‐control task is a convenient method for distinguishing individuals by fat discrimination ability when they are segmented using different criteria. Practical Applications: The four‐sample difference from control test for salad dressing was developed as a rapid screening tool for fat discrimination. The test was designed to fill gaps in our understanding of individual differences in fat discrimination and has practical applications for testing large numbers of respondents in consumer testing, clinical settings and genetic association studies.